Redistribution, state trading enterprises and 'politically optimal' tariffs. (14th November 2013) - McCorriston, Steve; MacLaren, Donald
Abstract: State trading enterprises (STEs) are widely used and can be viewed as instruments of trade policy. We analyse two aspects: the first is their potential trade distorting effect; the second is how they modify the case for the 'politically optimal' tariff. We show that the STE can reduce the need for a tariff designed for domestic redistribution. This result introduces some ambiguity about how STEs are interpreted: from a multilateralist perspective, they should be dealt with in the same way as other non‐tariff barriers; from a nationalistic perspective, they can reduce the need for 'politically optimal.' Abstract : Redistribution, entreprises d'État impliquées dans le commerce international, et tarifs 'politiquement optimaux .' Les entreprises d'État impliquées dans le commerce international (EEICI) sont communément utilisées comme instruments de politique commerciale. On analyse deux aspects de cette intervention : le premier est leur effet potentiel de distorsion sur les flux commerciaux; le second est jusqu'à quel point cette intervention modifie l'argument du tarif 'politiquement optimal.' On montre que les EEICI peuvent réduire le besoin d'un tarif défini pour des fins de redistribution au niveau domestique. Le résultat injecte une certaine ambiguïté dans le traitement des EEICI : d'un point de vue international, on devrait les traiter comme toute autre barrière non‐tarifaire; d'un point de vue nationaliste, ils peuvent réduire le besoin de faire appel au 'politiquement optimal.'